The president's call : executive leadership from FDR to George Bush - Michaels, Judith E., 1948- (Pitt series in policy and institutional studies., 1997)
Judith Michaels provides an in-depth examination of the Senate-confirmed presidential appointees of the Gorge H. W. Bush administration, and analyzes what these choices reveal about him, his administration, and the institution of political appointments itself. She compares this research to other administrations in the modern era. Particularly fascinating is how Bush's appointees compare with those of Ronald Reagan.